DEVELOPMENT OF CITIZENSHIP EDUCATION IN INDONESIAN - Afriadi, Bambang; Komarudin, Komarudin; Dudung, Agus (International Journal of Business, Law, and Education, 2023)
This article tries to contribute to building judgments based on many important issues. This study is intended to evaluate comprehensively, in this case, citizenship education as part of the curriculum. Systematic reviews are used to examine this study, which refers to a methodological combination in which a literature review is an important component. At the same time, assessment is a matching technique. Matching approach compares quality with criteria to a particular result. This study reveals that citizenship education and civil engagement is based on the belief that citizenhood education is a powerful instrument with the capacity to influence the future. Consider applying the ideas and practices of citizenship and intercultural education to international and local development. Global Citizenship, digital citizenship and media citizenships are concepts used in contemporary politics   Acknowledgment: This article is dedicated to the late Prof. Agus Dudung, as an intellectual example and personality nobility